Record book of the Westminster Monthly Meeting of the Society of Friends - Westminster Monthly Meeting of the Society of Friends
Record book containing photographs of minutes of the Westminster Monthly Meeting, Westminster, London, England, concerning the purported marriage of a Quaker, Hannah Lightfoot, to George III.
Chiefly photographic reproductions.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: George -- III, -- King of Great Britain, -- 1738-1820.; Lightfoot, Hannah, -- 1730-; Society of Friends -- England -- London; Westminster (London, England) -- History